UJI COBA PENGGUNAAN TEMPE SEBAGAI PENGGANTI KENTANG DALAM PEMBUATAN KUE LUMPUR - Abduh, Mohammad Syaltut (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
Mud cake is a moist cake that has a sweet taste and soft texture. the mud cake is generally made from potatoes as supporting the taste and texture, if combined with other materials would be too much carbohydrate in the mud cake. therefore this research will be used a substitute potatoes for tempe. Tempe has a solid texture than potatoes and has a lower carbohydrate than potato. This research used experimental method 1 is the control product that uses the sludge cake of potatoes 100% and 3 treatment product that uses 30% tempeh, 60% tempeh, 90% tempeh. Data obtained by distributing questionnaires to the two groups, the first group of expert panelists are as many as 5 people to know the difference between product control and treatment products, untrained panelists group of 25 people to determine whether it is acceptable by the general public. Results obtained through ANOVA test there is no real difference in terms of texture, flavor, aroma, color with control products. A test of the most preferred products is control product with value of 3,21, product of 60% tempeh with value of 3,14, product of 30% tempeh with of value 3,04, and product of 90% tempeh with value 2,72.